Neonatal Urinary Ascites due to Kinking of the Right Ureter - Darfioes Basir; Darlan Darwis; E.M. Halimun; Asril Aminullah (Paediatrica Indonesiana, 1978)
A case of neonatal urinary ascites in a female newborn infant due to kinkingof the right ureter is presented. The diagnosis was based on the following findings: clinically, the presence of ascites which was confirmed radiologically,and by abdominal parfacentesis; by I.V.P. and operatively. After operative relief of the obstruction, the ascites disappeared and on the 8th day after operation she was discharged in a good condition.